FOOD INSECURITY AMONG VULNERABLE HOUSEHOLDS: IMPLICATIONS ON POVERTY PERPETUATION IN IMO STATE - Ugomma Udogaranya, Joy; Osita-Njoku, Agnes; Anyaoha, Okechukwu (African Journal of Social and Behavioural Sciences, 2026)
This study examined food insecurity among vulnerable households in Imo State, Nigeria, with particular attention to income disparities, asset ownership, and household expenditure patterns. Using the Household Food Insecurity Access Scale (HFIAS), the study assessed the severity of food insecurity and explored how economic constraints shape household coping strategies. A descriptive survey design was adopted, involving 484 respondents drawn from vulnerable communities across eight Local Government Areas in Imo State. The study population comprised low-income households, female-headed households, widows, elderly persons living alone, and residents of rural and peri-urban areas. Data were collected through a structured questionnaire and analysed using both descriptive and multivariate techniques. Findings indicate that food insecurity is widespread and severe among vulnerable households, with a substantial proportion experiencing chronic food shortages. Food insecurity was strongly associated with low income levels and was found to undermine household asset ownership and distort expenditure priorities. Many households adopted adverse coping strategies, including skipping meals, reducing meal portions, and selling productive assets, actions that further entrenched their vulnerability and weakened long-term economic resilience. The study concludes that food insecurity in Imo State is not merely a short-term welfare issue but a structural challenge closely linked to poverty and livelihood instability. Addressing this challenge requires integrated policy responses that go beyond food aid. The study recommends targeted income-support programmes, household-level food subsidy initiatives, and community-based agricultural interventions to strengthen livelihoods, protect household assets, and enhance sustainable food access among vulnerable populations.